2011
DOI: 10.1088/0957-4484/22/50/505401
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanorod/CdS nanocrystal core/shell-type heterostructures for solar cell applications

Abstract: ZnO/CdS core/shell nanorod arrays were fabricated by a two-step method. Single-crystalline ZnO nanorod arrays were first electrochemically grown on SnO(2):F (FTO) glass substrates. Then, CdS nanocrystals were deposited onto the ZnO nanorods, using the successive ion layer adsorption and reaction (SILAR) technique, to form core/shell nanocable architectures. Structural, morphological and optical properties of the nanorod heterojunctions were investigated. The results indicate that CdS single-crystalline domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 50 publications
(89 reference statements)
1
83
0
Order By: Relevance
“…In the first stage ZnO NR were grown on a fluorine doped tin oxide (FTO)-glass substrate by potentiostatic electrodeposition in a three-electrode cell [6][7][8]. The sensitization stage used the previously deposited ZnO NR as a substrate for the deposition of CdS and CdTe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the first stage ZnO NR were grown on a fluorine doped tin oxide (FTO)-glass substrate by potentiostatic electrodeposition in a three-electrode cell [6][7][8]. The sensitization stage used the previously deposited ZnO NR as a substrate for the deposition of CdS and CdTe.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitizer used will be determinant in the posterior optical performance of the material; here the most important candidates are CdS or CdTe [4,5]. Previously reported ZnO/CdS NR core-shell array sensitized by Successive Ion Layer Adsorption Reaction (SILAR) shown an increased absorption in the visible [6][7][8]. Moreover, a dependence in the absorption edge position was observed for these samples with the NP size and CdS content in the samples [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,[21][22][23][24][25] Among these methods, the electrochemical deposition (ED) method has many advantages such as low growth temperature, simple and low cost process without the need for vacuum systems for preparing ZnO nanorods with high crystalline quality, well suited for scale-up and good electrical contact between structures and substrate. [22][23][24][25][26][27] Several studies of electrodeposition of ZnO NRAs have been reported in the literature. These studies showed the influence of deposition parameters such as growth temperature, zinc precursor concentration, pH, electrodeposition potential and growth time on controlling nanowire morphology, in particular the nanowire diameter and length (i.e.…”
mentioning
confidence: 99%